CITRA PEREMPUAN MESIR: TINJAUAN KRITIK SASTRA FEMINIS TERHADAP NOVEL WA NASÄªTU ANNÄª IMRAâAH KARYA IHSÄN ABDUL QUDDÅªS - , Muh. Luqman Arifin, Prof. Dr. Taufiq A. Dardiri, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The title of this study is "The Image of Egyptian Women: Overview of Feminist Literary Criticism Against The Novel âWa NasÄ«tu AnnÄ« Imra'ahâ written by IhsÄn Abdul QuddÅ«s. This study relies on an issue, that is the image of women in The Novel âWa NasÄ«tu AnnÄ« Imra'ahâ. This novel raised the issue of gender in relation to the power of the patriarchal world that still dominates Arab society with a social portrait of Egyptian background. The study theoretically aims at describing and revealing the image of women in the 1952 post-revolutionary in Egypt which covers subordination, stereotyping, and injustice images. In addition, it describes the feminist formula in the novel that provides insight for gender conscious. Practically this study aims to broaden the reader that women have equal capacity with men, if they are given the same rights and opportunities In this study, the image of women is diclosured by using a qualitative feminist literary criticism that type of collected data is qualitative in nature. The stages of study consist of critical reading of the defined object, collecting and analysing data and drawing conclusions. The results show that the image of women in the Arab-Egyptian culture, which is based on the culture of patriarchy is considered as stigmatized creature remains in the domestic sphere. Women should stay at home, take care of kitchen, raise children, do not need highly educated, and active in the public sphere.